A Taxonomic Revision of the Himalayan Firs - Jain, K. K. (Indian Forester, 1975)
An extensive survey of the Abies populations in the various parts of the Himalayas was undertaken and the details of morphological as well as anatomical characters were studied to resolve the problem of the fir complex in the Himalayas. In the Western Himalayas there are two distinct species of Abies, a high altitude one A. spectabilis and a low altitude one A. pindrow. Hybrid populations in the intermediate zones are met all through. Brandis’s alticlinal concept in the light of the present investigations does not hold good as there is no gradual change in traits of A. pindrowtowards A. spectabiliswith the increasing elevation. Characters morophological as well as anatomical, particularly the position of the resin canals in the leaf distance between the two vascular bundles in the leaf, the distribution pattern of the stomata on the leaf surface, the nature of the horizontal walls of the vertical parenchyma in the wood and the wood rays height are all in favour of maintaining two distinct species, with their putative hybrids in the middle of the range. The East-Himalayan fir species differs in many traits from the West-Himalayan high altitude species, A. spectabilis and has been identified as Abies forrestii C.C.Rogers.